Hakikat dan Keterkaitan Manusia dengan Pendidikan - Weni Hamdina; Tuti Susanti; Jon Hendri; Doni Aizus Idris; Hendrizal Hendrizal (Lembaga Pengembangan Kinerja Dosen, 2024)
Primary education is an important phase in the formation of the foundation of knowledge, skills and values for each individual. Policies for managing basic education units are critical to ensuring equitable access to and quality of education. This article explores the nature of basic education management policy, from its philosophical foundation to its implementation process. The literature study method is used to analyze relevant literature and policy documents, which provide an overview of the historical evolution of basic education management from pre-modern times to the contemporary era. The results illustrate the complexities and challenges in policy planning, implementation and evaluation, and the importance of effective supervision. It is hoped that this in-depth understanding can improve the effectiveness of basic education policy and management globally.